Chapter Il lavoro nell’operaismo italiano - MEZZADRA, SANDRO (Firenze University Press, 2025)
The chapter deals with a specific current of Marxist thought that took shape in the 1960s in Italy, Operaismo, also known as autonomist Marxism. Against the background of powerful workers’ struggles in the North of the country, journals like Quaderni rossi and Classe operaia pursued an innovative investigation (“co-research”) of the condition and composition of labor in a conjuncture of accelerated mass industrialization. The chapter discusses the ways in which two leading figures of Operaismo, Mario Tronti and Toni Negri, took stock of the outcomes of that investigation in their reading of Marx, in their theoretical reflections on the concept of labor, and in the politics of “refusal” they proposed with different inflections in the 1960s and in the 1970s. A politics of refusal emerges from the work of both authors, although their conclusions.